2019
DOI: 10.1111/jcms.12852
|View full text |Cite
|
Sign up to set email alerts
|

Liberty: Security dilemmas and party cohesion in the European Parliament

Abstract: The European Parliament is an increasingly central actor in attempts to regulate surveillance and find the balance between safeguarding personal freedoms and ensuring EU citizens' security. However, virtually nothing is known about what drives the positions of MEPs on this issue, or about how the cohesion of European parties is affected by these attempts. We explore this subject and propose a novel theoretical framework focusing on the interplay between the characteristics of the two principals of the MEPs -Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…So do national interests. The literature has shown that the left-right dimension matters the most when issues of redistribution and regulation are at stake (Cavallaro et al, 2018;Chiru & Stoian, 2019;Hooghe et al, 2002) resulting in a weaker, albeit still visible voting cohesion on economic and market policies, such as industrial policy or labour market policies, which touch upon these issues in multiple ways. In other words, we expect right-left ideology within the Eurosceptic votes to matter more in some policy fields than in others.…”
Section: Theorising Eurosceptic Contestation In the Epmentioning
confidence: 99%
“…So do national interests. The literature has shown that the left-right dimension matters the most when issues of redistribution and regulation are at stake (Cavallaro et al, 2018;Chiru & Stoian, 2019;Hooghe et al, 2002) resulting in a weaker, albeit still visible voting cohesion on economic and market policies, such as industrial policy or labour market policies, which touch upon these issues in multiple ways. In other words, we expect right-left ideology within the Eurosceptic votes to matter more in some policy fields than in others.…”
Section: Theorising Eurosceptic Contestation In the Epmentioning
confidence: 99%
“…MEPs' behaviour at rollcall votes is the most studied area of legislative behaviour inside the European Parliament (Hix & Høyland, 2014). While there is consensus that ideological orientation on the left-right and EU integration dimensions structure party competition in the EP, scholars debate the extent to which MEPs follow the preferences of their national parties or their EPG, and how timing and differences in positions and issue salience between the two principals affect voting behaviour (Chiru & Stoian, 2019). We therefore use roll-call votes as an indicator of the extent to which PRR MEPs' follow a common agenda that may directly translate into policy outcomes.…”
Section: From Democratic Backsliding To Prr Polity-based Contestationmentioning
confidence: 99%
“…With the EP's 2009 amendment of its Rules of Procedure, roll-call voting is now required for all final legislative votes. As a result, roll-call voting has become a more reliable, mainstream data source in EP scholarship (Cencig and Sabani, 2017; Chiru and Stoian, 2019; Hix et al, 2018; Hug, 2016; Kaniok and Mocek, 2017; Lindstädt et al, 2012; Yordanova and Mühlböck, 2015). As the EP has increased its role in EU external affairs, EP roll-call voting records in external affairs provide an untapped resource for EP scholars.…”
Section: European Parliament Voting and Foreign Policymentioning
confidence: 99%
“…Yet, studies that focus specifically on MEPs’ voting behaviour in foreign policy are missing, with a few exceptions: Chiru and Stoian (2019) analyse MEPs voting on directives relating to surveillance and the fight against terrorism; Norrevik (2020) analyses MEPs’ policy positions on comprehensive trade agreements with third countries. Relating specifically to the EU–Russia relationship, Braghiroli (2015) analyses the role of MEPs’ party group affiliation and nationality and their stance towards Russia using EP voting records between 2004 and 2012.…”
Section: European Parliament Voting and Foreign Policymentioning
confidence: 99%